2023
DOI: 10.3390/jcm12237294
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Medical Landscape of Anorexia Nervosa over a Decade: A Retrospective Study of Possible Physical and Psychological Shifts

Paolo Meneguzzo,
Lorenza Di Pascoli,
Maria Bindolo
et al.

Abstract: In recent years, the definition, clinical characteristics, and psychological aspects of anorexia nervosa (AN) have undergone notable changes, influenced by various factors such as biology, psychology, and the environment. The COVID-19 pandemic is one such external factor that has been preliminarily identified as affecting the clinical presentation of AN. This study specifically aims to assess the alterations in psychological and medical features observed in individuals with AN during the pandemic. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Interestingly, peri-pandemic AN participants reported less severe general ED symptomatology, perceived less concerns about diet, body weight and body shape compared to pre-pandemic AN participants. This appears to be in contrast with previous literature with a comparable case–case study design which showed either an increase in binge eating episodes [ 30 ] a trend towards more food restraint [ 29 ], or no significant differences in ED symptoms [ 28 ] among adolescents with an ED peri-pandemic versus pre-pandemic. The observed discrepancy could be explained by differences between the respective populations, e.g., age, severity of illness, duration of illness, specific time period during the pandemic, or differences in COVID-19 regulations imposed by different governments in response to the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, peri-pandemic AN participants reported less severe general ED symptomatology, perceived less concerns about diet, body weight and body shape compared to pre-pandemic AN participants. This appears to be in contrast with previous literature with a comparable case–case study design which showed either an increase in binge eating episodes [ 30 ] a trend towards more food restraint [ 29 ], or no significant differences in ED symptoms [ 28 ] among adolescents with an ED peri-pandemic versus pre-pandemic. The observed discrepancy could be explained by differences between the respective populations, e.g., age, severity of illness, duration of illness, specific time period during the pandemic, or differences in COVID-19 regulations imposed by different governments in response to the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the current study collected data during a more extensive period during the pandemic (March 2020–October 2021), while previous studies [ 28 , 29 ] collected data during a relatively short period during the pandemic (6–9 months). The study by Meneguzzo [ 30 ] conducted a study on a patient population that was relatively comparable to ours. However, their patient population had a slightly longer disease duration and their study was conducted in another country with different COVID-19-related restrictions at that specific time point.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Recently, it has also been proposed to consider the COVID-19 pandemic as a collective trauma or psychotrauma due to the presence of globally shared emotional connections arising from the discrepancy between the threat and coping abilities [ 24 ]. However, these aspects are not definitive, even though the pandemic has shed light on the relevance of environmental factors in EDs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%